Changes in individuals’ glaucoma progression velocity after IOP-lowering therapy: A systematic review - Vihar Naik; Simran Ohri; Elise Fernandez; Jean-Claude Mwanza; David Fleischman (PLoS ONE, 2025)
Primary open-angle glaucoma (POAG) is a chronic progressive optic neuropathy often associated with increased intraocular pressure (IOP). Monitoring glaucoma progression velocity, for example, the rate of change in global indices such as mean deviation (MD), is a common way to determine whether functional deterioration has occurred. This systematic review aims to assess changes in glaucoma progression velocity in response to IOP-lowering therapy at an individual level. A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A comprehensive search of PubMed, Cochrane CENTRAL, and ClinicalTrials.gov from database inception through November 12, 2023, was conducted for randomized clinical trials involving patients with POAG, normal tension glaucoma, or progressive ocular hypertension who received IOP-lowering therapy with a target IOP reduction ≥20% from baseline. Included trials were required to report visual field progression velocity information for individual patients before and after intervention. One study was found to meet inclusion criteria and, therefore, synthesis of data and meta-analysis were unable to be performed. The study reports on 139 eyes of 109 patients from the Ocular Hypertension Treatment Study who reached a POAG endpoint. In these patients, the post-treatment rate of MD change (−0.27 ± 0.7 dB/year) was significantly slower than the pre-treatment rate (−0.51 ± 0.8), P < 0.01. In addition, the rate of MD change significantly correlated with mean IOP reduction (p < 0.001). The singular study demonstrated that IOP-lowering therapy did variably slow glaucoma progression rate in that patient cohort. There is a need for more studies that focus on individual patients’ responses to glaucoma treatment. Furthermore, this information should be used to classify the magnitude of patients’ responsiveness to IOP reduction. Future studies should report pre- and post-intervention progression velocities.